Aktivitas antimikroba dan antioksidan ekstrak tepung daun dan buah mengkudu (Morinda citrifolia) - David Kurniawan (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
Noni fruit is a medical plant with active compound like antimicrobial and antioxidant that could potentially be used as a feed additive in poultry. This study aimed to determine the activity antimicrobial and antioxidant of noni fuit leave and fruit extract. The method was field experiment arranged in Completely Randomize Design with 3 treatments and 3 replications. The treatments are metanol extract of noni fruit powder, leave noni powder and combination noni fruit and leave powder. The inhibition zone diameter was determined by disc diffusion method, total phenol was determined by Folin-Ciocalteu method, Flavonoid was determined by Aluminium clorida method and antioxidant activity by DPPH (1,1-Diphenyl-2picrylhydrazyl) method. The results showed that noni powder ex-tract had significantly effect (P<0.01) in inhibition of Lactic Acid Bacteria and Escherichia coli. The total phenol of Noni fruit powder is highest approximately 1.67 mg/g GAE. The flavonoid of Noni leave is highest approximately 0.0438 mg/g QE. The DPPH test of Noni fruit is highest approximately 84.03%. It can be concluded that noni fruit extract can be used as an antibacterial and antioxidant in poultry.